2020
DOI: 10.1002/eat.23453
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐based anorexia disrupts systemic oxidative state and induces cortical mitochondrial fission in adolescent female rats

Abstract: Objective Patients with Anorexia Nervosa (AN) display increased levels of oxidative stress that correlates with disease severity. Unfortunately, the biological ramifications of AN‐induced oxidative stress on the brain are largely unknown. Our lab uses the preclinical activity–based anorexia (ABA) paradigm to model symptoms of AN. The goal of the present study was to determine how ABA experience affects oxidative state and its consequences in adolescent female rats. Method We compared systemic glutathione and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…We have previously shown that pathological weight loss does not occur in all rats exposed to ABA conditions, and in fact a subpopulation of rats remains resistant to weight loss when exposed to the same experimental conditions (Milton et al, 2018). These susceptible and resistant subpopulations have been replicated in other studies investigating the neurobiology of AN in ABA rats (Hurley, Murlanova, et al, 2021) and mice (Beeler et al, 2020), supporting the use of the ABA model for examining predictors of pathological weight loss.…”
Section: Introductionmentioning
confidence: 55%
“…We have previously shown that pathological weight loss does not occur in all rats exposed to ABA conditions, and in fact a subpopulation of rats remains resistant to weight loss when exposed to the same experimental conditions (Milton et al, 2018). These susceptible and resistant subpopulations have been replicated in other studies investigating the neurobiology of AN in ABA rats (Hurley, Murlanova, et al, 2021) and mice (Beeler et al, 2020), supporting the use of the ABA model for examining predictors of pathological weight loss.…”
Section: Introductionmentioning
confidence: 55%
“…These studies demonstrate that, like in patients with AN, ABA rodents have decreased brain volume that is reversed by re-feeding [ 11 14 , 15 •]. Weight loss is also associated with increased markers of oxidative stress in the prefrontal cortex that is reversed by weight restoration [ 16 ]. The ABA model provided new insights into the impact of AN on the brain by identifying reductions in astrocyte number and proliferation in the cerebral cortex without a change in neuronal number [ 15 •].…”
Section: Aba Paradigm: Classical Approachesmentioning
confidence: 99%
“…We have previously shown that pathological weight loss does not occur in all rats exposed to ABA conditions, and in fact a subpopulation of adolescent female Sprague-Dawley rats remain resistant to weight loss, even when exposed to the same experimental conditions [41]. These susceptible and resistant subpopulations have been replicated in other studies investigating the neurobiology of AN in ABA rats [42] and mice [43], supporting the use of the ABA model for examining behavioural and immune phenotypes that predispose animals to pathological weight loss.…”
Section: Introductionmentioning
confidence: 61%